The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/bcp.14695
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lipophilic vs hydrophilic statins on the clinical outcome and biomarkers of remodelling in heart failure patients: A prospective comparative randomized study

Abstract: Aims There are insufficient direct comparative studies addressing the impact of the type of statin on their respective efficacy in heart failure (HF). The aim of the current study was to compare the effects of lipophilic (atorvastatin) vs hydrophilic (rosuvastatin) on left ventricular function, inflammatory and fibrosis biomarkers in patients with chronic HF. Methods This was a prospective, randomized, comparative, parallel study. A total of 85 patients with chronic HF optimized on guideline directed therapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…The reason why mesalazine affected perivascular fibrosis in particular might be due to the pharmacological distribution of the hydrophilic compound. For the use of statins after MI, it has been demonstrated that the lipophilic atorvastatin offered advantages such as increasing left ventricular EF and reducing fibrosis marker expression over the hydrophilic rosuvastatin (El Said et al, 2021 ). The authors attribute this observation to increased extrahepatic tissue penetration of the lipophilic agent (El Said et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason why mesalazine affected perivascular fibrosis in particular might be due to the pharmacological distribution of the hydrophilic compound. For the use of statins after MI, it has been demonstrated that the lipophilic atorvastatin offered advantages such as increasing left ventricular EF and reducing fibrosis marker expression over the hydrophilic rosuvastatin (El Said et al, 2021 ). The authors attribute this observation to increased extrahepatic tissue penetration of the lipophilic agent (El Said et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the use of statins after MI, it has been demonstrated that the lipophilic atorvastatin offered advantages such as increasing left ventricular EF and reducing fibrosis marker expression over the hydrophilic rosuvastatin (El Said et al, 2021 ). The authors attribute this observation to increased extrahepatic tissue penetration of the lipophilic agent (El Said et al, 2021 ). Similar observations were made in the treatment of tuberculosis, in which lipophilic antibiotics displayed higher anti‐tuberculosis activity (Piccaro et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In support of the direct influence of the lipophilic statins on the brain cholesterol come the findings of more frequent associations of cognitive impairments with the recent use of atorvastatin and simvastatin [76,77], which are lipophilic statins, as well as the findings of Rojas-Fernandez and colleagues, who showed that switching from a lipophilic to a hydrophilic statin might resolve the cognitive impairment [78]. The differences between the two classes of statins in cardiac outcomes are also not settled: while a meta-analysis showed similar effects of the two types of statins in coronary artery disease [79], the lipophylic atorvastatin in 40 mg daily dose was superior in increasing left ventricular ejection fraction and in reducing markers of fibrosis in patients with heart failure as compared to the hydrophilic rosuvastatin in daily doses of 20 mg over 6 months [80].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing the effects of atorvastatin vs. rosuvastatin on left ventricular function, inflammatory and fibrosis biomarkers in patients with chronic HF, published by El Said et al ( 47 ) suggested that the impact of lipophilic atorvastatin was greater than that of hydrophilic rosuvastatin in HF patients with regards to the improvement in left ventricular ejection fraction and soluble suppression of tumorigenicity reduction, a novel fibrosis marker.…”
Section: Statin Solubility and Cardiovascular Outcomesmentioning
confidence: 99%